Population displacement and urban conflict: Global evidence from more than 3300 flood events (2021)
In this paper, we study the effect of displacement of population into cities on urban conflict in developing countries. To do so, we construct a novel measure of exposure to floods, using data on more than 3,300 flood events worldwide, as an exogenous source of population displacement. We combine this with city level observations of more than 9,000 urban social disorder events. Exposure to floods is found to be associated with higher likelihood and frequency of urban social disorder. Our evidence suggests that the effects of floods on urban disorder occur mainly through the displacement of population into large cities. Exploring the information on urban disorder events in more detail, we find that the association between city growth and urban disorder is strongest for events related to public service provision, wages and food prices.